External match load in amateur soccer: the influence of match location and championship phase - Miguel, Mauro (2022)
Assessment of the physical dimension implicit in the soccer match is crucial for the improvement and individualization of training load management. This study aims to: (a) describe the external match load at the amateur level, (b) analyze the differences between playing positions, (c) verify whether the home/away matches and if (d) the phase (first or second) of the championship influence the external load. Twenty amateur soccer players (21.5 ± 1.9 years) were monitored using the global positioning system. The external load was assessed in 23 matches, where 13 were part of the first phase of the competition (seven home and six away matches) and the other 10 matches belonged to the second (and final) phase of the championship (five home and five away matches). A total of 173 individual match observations were analyzed. The results showed significant differences between playing positions for all the external load measures (p < 0.001). There were higher values observed in the total distance covered for central defenders (p = 0.037; ES = 0.70) and in high-intensity decelerations for forwards (p = 0.022; ES = 1.77) in home matches than in away matches. There were higher values observed in the total distance (p = 0.026; ES = 0.76), relative distance (p = 0.016; ES = 0.85), and moderate-intensity accelerations (p = 0.008; ES = 0.93) for central defenders, in very high-speed running distance for forwards (p = 0.011; ES = 1.97), and in high-intensity accelerations (p = 0.036; ES = 0.89) and moderate-intensity decelerations (p = 0.006; ES = 1.11) for wide midfielders in the first phase than in the second phase of the championship. Match location and championship phase do not appear to be major contributing factors to influence the external load while the playing position should be used as the major reference for planning the external training load.